Pengembangan Aplikasi Penggajian Karyawan Berbasis Web Menggunakan Metode Waterfall - Bagus Wahyudianto; Hendra Setiawan Sunarya; Heri; Muhammad Mufid Aqil; Aries Saifudin (CV. Multi Kreasi Media, 2024)
Management of salaries and wages of employees is important in the management of human data sources in the company. In the digital era, the use of technology can help simplify and speed up the payroll process. Therefore, this study aims to develop a web-based employee payroll application that helps in managing employee salaries and wages more efficiently and effectively. This web-based employee payroll application features employee data management, employee salary and wage data management, and payroll reports. This application is built using web technology so that it can be accessed through a web browser without the need to install additional software. Waterfall software development method and PHP programming language and MySQL database are used in the development process of this application. Testing and validation of the application is done by the method of black box testing and user acceptance testing. The results of this study show that the developed web-based employee payroll application can help companies in managing employee payroll more effectively and efficiently.